Isolation and genomic analysis of phage BUCT551 against drug-resistant Aeromonas hydrophila - Han, Pengjun; Qin, Hongbo; Hao, Chenxi; Du, Zhiping; Yang, Yang (Frontiers in Veterinary Science, 2025)
Aeromonas hydrophila (A. hydrophila) is a common pathogen in aquaculture that also causes opportunistic infections and sporadic food- and water-borne illness in humans. Phage therapy is increasingly considered a promising complementary medicine for antibiotic therapy. In this study, we isolated a novel A. hydrophila phage (designated BUCT551) using A. hydrophila strain Ah18 as an indicator. The one-step growth curve demonstrated that BUCT551 had a latent period of 20 min and a burst size of 32 PFU/cell at its optimal multiplicity of infection (0.1). BUCT551 had a survival pH range from 5 to 10 and could tolerant temperatures from 4 °C to 50 °C. Host range analysis showed that the phage was able to lyse not only A. hydrophila, but also Aeromonas veronii. Whole-genome sequencing of BUCT551 revealed a linear DNA genome of 61,382 bp. Bioinformatics analysis demonstrated that the genome of phage BUCT551 contains 74 predicted open reading frames (ORFs), of which 27 were annotated as functional proteins with assigned biological roles. Notably, no lysogeny-associated genes, antimicrobial resistance determinants, virulence factors, or tRNA genes were identified in this phage genome. A comparative genomic analysis showed that phage BUCT551 is the closest relative to Aeromonas phage LAh_7 and shares the same new branch in the phylogenetic tree. Characterization of the phage BUCT551 enriches our knowledge about the diversity of A. hydrophila phages.